Students and Teachers Perceptions toward the Use of Blogs in Literature Reviews’ Writing A Case Study of Master II Students of English Department and Teachers of Mathematics and Computer Science Department Amar Telidji University -Laghouat - Benguettache, Dahiba; Bensaidane , Fatima; Boumediene ,Houda (Faculty of Letters and Foreign Languages Department of English, 2019)
The current research paper aims to investigate if the blog use could be as an effective tool to gather information and to facilitate writing literature reviews through collecting sources. It seeks to find answers to whether blogging can be used as a research tool to gather information and what are the perceptions of both teachers and students towards the use of such a tool in writing literature reviews? The selected participants represent 10% of the whole population; 13 students from Master Two of English Department and 7 teachers from Mathematics and Computer Science Department at Amar Thelidji University – Laghouat were selected randomly as samples. The descriptive method was adopted and data was collected through two questionnaires. The results demonstrated that blogs are effective tools in gathering literature and to write reviews, and both teachers and students are satisfied with them. The use of blogs facilitates the process of literature reviews writing. Therefore, we recommend the future researchers to use them in writing their reviews